Composite Astringent Index and the Determination of Anti-infective Properties of Selected Folklore Therapies - Wagarachchi, A. N.; Dilshan, W. G. L.; Pathirana, W.; Wijayabandara, M. D. J.; Siriwardhene, M. A.; Obeysekera, C. (My University, 2020)
Purpose: An attempt was made to quantify comparative astringent powers among selected substances taking tannic acid as the reference standard. The measurements were to be based on composite astringent power of all contributing compounds present in extracts. Among the folklore antimicrobial measures, consumption of black tea and black coffee in diarrheal conditions are well established. Their effectiveness was to be determined through demonstration of reduction in bacterial colony counts. Method: Astringent power of selected materials were determined using standard egg albumin solution by titrating with different astringent preparations. End points were determined when protein precipitation was completed using UV absorption measurements and biuret test. To evaluate anti-microbial activity of black tea and black coffee infusions, experiments on growth inhibition by a reduction of colony forming units were carried out. Results: The strongest astringent activity was found with Terminalia chebula (aralu) extract and the weakest with coriander extract. Black tea and black coffee infusions showed a high percentage of inhibitory activity against both Escherichia coli and Salmonella typhi in a range 70.83%±3.6 to 87.50%±0.00. Conclusion: Using astringent power of substances, the Composite Astringent Index was established. It was clear that consumption of black tea and black coffee infusions during diarrheal states can achieve significant anti-diarrheal effects. Materials with greater astringency showed greater anti-diarrheal effects. Materials with minimum end point values for the protein precipitation assay yielded the lowest astringent power values
Keywords: Composite Astringent Index; Protein precipitation; Black tea; Black coffee; Folklore medicine.